Upaya Peningkatkan Status Pengetahuan Kesehatan Gigi dan Mulut pada Masyarakat dengan Metode Penyuluhan FlipChart dan Video di Desa Lanna - Sari Aldilawati; Muhammad Fajrin Wijaya; Nur Rahmah Hasanuddin (Idea Pengabdian Masyarakat, 2021)
This community service is carried out as a form of the Tri Dharma of Higher Education, community service by raising the theme of the importance of maintaining and maintaining dental and oral health in children, pregnant women and the elderly. Dental and oral disease is one of the public health problems in Indonesia. This is based on reports of the high prevalence of sufferers of the disease, and is one of the top ten sequences of diseases that are most often complained of by the public. Dental and oral health is closely related to body health. The condition of the mouth and teeth that are not maintained will cause many problems and discomfort. In an effort to get good oral and dental health, awareness is needed to implement a healthy lifestyle by diligently brushing teeth properly and correctly. The purpose of this service is to provide understanding to the community, pregnant women and the elderly about the importance of maintaining and maintaining dental and oral health. The method of implementing community service with direct counseling techniques to the community. The results of the service, in general the counseling participants have an increased understanding of maintaining and maintaining dental and oral health. The conclusion of this service is the importance of continuous education and counseling to the community regarding the importance of maintaining and maintaining dental and oral health in children, pregnant women and the elderly.